Village Seed Bank for achieving seed self sufficiency - Khuntia, Debi Prasanna (Indian Farming, 2015)
Having a Village Seed Bank is a good idea to help the farmers ingetting quality seeds. Odisha is one such state where farmers’ need for quality seeds is met by the seed bank which supplies seeds through various seed supply systems.